2018
DOI: 10.1371/journal.pone.0197443
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in associations between multimorbidity and physical function domains among community-dwelling adults in Singapore

Abstract: ObjectivesThe aims of the study were to identify the associations between multimorbidity and specific physical function domains among community-dwelling adults in Singapore, and to examine sex differences in the associations.MethodsThis study was conducted using baseline data of 1,940 participants in the Population Health Index Survey conducted in the Central Region of Singapore from November 2015 to November 2016. Physical function was assessed using the Function Component of the Late-life Function and Disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 48 publications
4
36
0
1
Order By: Relevance
“…There is no strict definition of "middle-age" and studies have defined it as age between 40-65 years 22 or 45-64 years. 3,5,23 In our study, the lower age limit was defined as 40 years old as that is also the minimum age at which general health screening is recommended. 6 According to the Singapore census those aged 65 years and above are considered elderly 21 and hence the upper limit of our middle-age range was defined as 64 years old.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no strict definition of "middle-age" and studies have defined it as age between 40-65 years 22 or 45-64 years. 3,5,23 In our study, the lower age limit was defined as 40 years old as that is also the minimum age at which general health screening is recommended. 6 According to the Singapore census those aged 65 years and above are considered elderly 21 and hence the upper limit of our middle-age range was defined as 64 years old.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 About 30-58% of middle-aged patients have multimorbidity, 2−4 and the absolute number of these patients may even exceed that of elderly patients. 3 A survey of the general population in Singapore found that 35% of middle-aged participants had multimorbidity 5 and although there are no official estimates in the Singapore primary care setting, the figure is likely to be higher. The prevalence of multimorbidity rises steeply in midlife and plateaus in those aged 75 years and above, 2 and this may be contributed by the growing emphasis on screening and early detection of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Multimorbidity and disability, which are related to but also distinct from frailty [28,29], were commonly adjusted in studies examining the association between frailty and healthcare utilisation [8,13]. We controlled for multimorbidity as a dichotomous variable (yes / no) which was de ned as the presence of two or more of the following 17 chronic conditions: dyslipidemia, high blood pressure, diabetes, chronic kidney disease, heart attack / ischemic heart disease, heart failure, stroke / transient ischemic attack, asthma, chronic bronchitis / emphysema / chronic obstructive pulmonary disease, cancer, osteoarthritis / gout / rheumatoid arthritis, osteoporosis, depression, anxiety disorder, schizophrenia, dementia / Alzheimer's, and Parkinson's disease [20]. Disability, which was determined based on whether assistance was required in any of the ten activities of daily living (ADLs) (yes / no) measured using the Modi ed Barthel Index [30], was also controlled in the models.…”
Section: Other Variablesmentioning
confidence: 99%
“…The baseline data of PHI which were collected during November 2015 to November 2016 were used for this study. The sampling procedure and survey methodology of the baseline PHI study has been described elsewhere [19][20][21]. In brief, eligible participants (Singapore citizens or permanent residents, aged 21 years and above and lived in the selected housing unit for the past six months) staying in randomly selected household units in the Central Region of Singapore were identi ed via door-to-door visits by trained surveyors and one eligible household member was randomly selected using Kish grid [22].…”
Section: Study Participantsmentioning
confidence: 99%